ANTIBIOTIC SUSCEPTIBILITY PROFILE AND SLIME LAYER FORMATION OF A CLINICAL ISOLATE OF STREPTOCOCCUS SANGUINIS FROM INFECTED ROOT CANALS - Ramadhan, Mohammed M.; F. Ali , Jassim (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study examined susceptibility of the clinical isolate Streptococcus sanguinis, isolated from an infected root canal to various antibiotics, and tested its capacity to form a slime layer. Method: PCR and gel electrophoresis both confirmed it as bacterial identification. The 16S rRNA gene sequence of S. sanguinis was determined and compared to previously determined sequences in the NCBI (National Center for Biotechnology Information) database. Growth of the isolate was determined to consist of a strong ability to form a slime layer when grown on Congo red-modified Schaedler agar medium. Results: GenBank records for the resulting sequences are under the accession numbers PQ654829 and PQ654911. The antibiotic susceptibility profile was high to levofloxacin, moderate to gentamicin, tobramycin and vancomycin, and complete resistance to cefixime. Novelty: The results of this study provide important information about the bacterium's virulence and antibiotic resistance.